Downregulation of the UDP-arabinomutase gene in switchgrass (Panicum virgatum L.) results in increased cell wall lignin while reducing arabinose-glycans - Willis, Jonathan D.; Smith, James; Mazarei, Mitra; Zhang, JiYi; Turner, Geoffrey; Decker, Stephen R.; Sykes, Robert; Poovaiah, Charleson; Baxter, Holly; Mann, David; Davis, Mark; Udvardi, Michael; et al. (Frontiers in Plant Science, 2016)
Switchgrass (Panicum virgatum L.) is a C4 perennial prairie grass and a lignocellulosic biofuels feedstock. Saccharification and biofuel yields are inhibited by the plant cell wall’s natural recalcitrance against enzymatic degradation. Plant hemicellulose polysaccharides such as arabinoxylans structurally support and crosslink other cell wall polymers. Grasses have predominately Type II cell walls that are abundant in arabinoxylan, which comprise nearly 25% of aboveground biomass. A primary component of arabinoxylan synthesis is uridine diphosphate (UDP) linked to arabinofuranose (Araf). A family of UDP-arabinopyranose mutase/reversible glycosylated polypeptides (UAM/RGPs) catalyze the interconversion between UDP-arabinopyranose (UDP-Arap) and UDP-Araf. In switchgrass we knocked down expression of the endogenous PvUAM1 gene via RNAi to investigate its role in cell wall recalcitrance in the feedstock. PvUAM1 encodes a switchgrass homolog of UDP-arabinose mutase, which converts UDP-Arap to UDP-Araf. Each transgenic line contained between one to at least seven T-DNA insertions, resulting in some cases, a 95% reduction of native PvUAM1 transcript in stem internodes. Transgenic plants had increased pigmentation in vascular tissues at nodes, but were otherwise morphologically similar to non-transgenics. There was decreased cell wall-associated arabinose in leaves and stems by over 50%, but there was an increase in cellulose in these organs. In addition, there was a commensurate change in arabinose side chain extension. Cell wall lignin composition was altered with a concurrent increase in lignin content and transcript abundance of lignin biosynthetic genes in mature tillers. Enzymatic saccharification efficiency was unchanged in the transgenic plants relative to the control, but had increased glucose in cell walls. The increased glucose detected in stems and leaves indicates that attenuation of PvUAM1 expression might have downstream effects on starch, cellulose and xyloglucan biosynthesis. A decrease in cell wall-associated arabinose was expected, which was likely caused by fewer Araf residues in the arabinoxylan. The decrease in arabinoxylan may cause a compensation response to maintain cell wall integrity by increasing cellulose and lignin biosynthesis. In cases in which increased lignin is desired, e.g., feedstocks for carbon fiber production, down-regulated UAM1 coupled with altered expression of other arabinoxylan biosynthesis genes might result in even higher production of lignin in biomass.